Creative tourism in the political agenda: possibilities for contributing to the sustainable development goals - Silva, Luana Alexandre; Paiva Júnior, Fernando Gomes de; Santana, Rebeka Cristiny Barbosa de (Revista Turismo em Análise, 2021)
The promotion of creative tourism has been established as part of the public policies adopted to foster the creative economy in tourist destination territories. As the particular creative and cultural practices of a region are valued by the active involvement among the participants, this cultural tourism approach presents itself as a favorable modality to the sustainable development of that location. The United Nations seeks sustainability by bringing together, in the 2030 Agenda, the Sustainable Development Goals (SDG), intended to guide public policy makers in favor of economic, social, and environmental parameters. The purpose of the study is to understand how certain public policies to promote creative tourism align with the SDG number 11, which proposes the construction of sustainable cities and communities. The single case study was carried out from the documentary research of the Creative Tourism Plan instituted in the municipality of Recife, Pernambuco, Brazil. The results from the content analysis indicate that the formulation of such a Plan tends to contribute to the achievement of the goals proposed by Agenda 2030 in terms of urbanization, management of territories, and valorization of cultural and natural heritage. The proposed public policy demands emphasis on infrastructure factors related to security, social equality, housing, inclusion of people in vulnerable situations, and protection of intellectual and environmental heritage.